Correlation between thoracic perimeter and body weight in Saanen and Saanen-Boer crossbred caprine - Magiero, Karen Purper Freitas; Pimentel, Viviane Antunes; Malafaia, Pedro Antônio Muniz; Deminicis, Bruno Borges (Scientia Agraria Paranaensis, 2020)
Among the animal data, we have biometric measures related to the development and production of goats. Thus, the objective of this study was to evaluate the correlation between live weight and thoracic perimeter in the caprine species, in order to obtain a barometric tape to estimate the live weight of the animal, without the use of the scale. Caprines from 10 to 42 kg live weight were used; males and females; pure Saanen race and Saanen-Boer crossbred. The thoracic perimeter of each animal was measured after weighing, in which it was measured at the external circumference of the thoracic cavity, just below the axillae, with steel cable to minimize possible errors from the elasticity of the tape measure, with the animal in the correct position of legs angulations. All parameters were recorded with the fasting animal for 12 h. Subsequently the live weight was estimated by regression equations with high correlation coefficients. The study showed a strong positive correlation between live weight (kg) of the animal and the thoracic perimeter (cm). The barometric tape for Saanen and Saanen x Boer crossbreed presented 97% efficacy for the estimation of the weight of Saanen and crossbreed. The thoracic perimeter provides a high efficiency in the estimation of the live weight of caprines and can be used as an alternative when scales are not available, being more appropriate the separation by race and sex before adjusting the equation to be calculated.